Konstruksi Latar dalam Fiksi Etnografis Orang-Orang Oetimu - Banda, Maria Matildis (Stilistika : Journal of Indonesian Language and Literature, 2021)
This paper examines the setting construction in the ethnographic fiction of Orang-Orang Oetimu by Felix K. Nesi. Analytical descriptive methods, oral tradition, narratology, and setting theory were used to answer questions about: colonial and decolonial settings, socio-educational, ethnographic, and military violence setting. The results depict that the colonial and decolonial grounds left scars on the nation, which experienced previous neglect and alienation in their land. This long-experienced trauma affects massive social, education, and military violence behaviors. In addition, colonial and decolonial history also intersects with ethnographic, mainly traditional beliefs about local history and myths about “sifon,” which is a tradition of having sex after circumcision. Unpredictable and irreversible patterns of colonial, decolonial, and ethnographic settings are also shockingly strengthening the plot, proofing that the well-constructed set produces quality and innovative story, narrative, and narrating.